HUBUNGAN FAKTOR-FAKTOR PENYEBAB KECEMASAN DENGAN TINGKAT KECEMASAN SUAMI MENGHADAPI ISTRI YANG BERSALIN SPONTAN DI POLINDES GERUNG UTARA - Nurul Hikmah Annisa (Jurnal Akademika Baiturrahim Jambi, 2019)
The husband feels anxious when accompanying a maternity wife who is influenced by several factors associated with anxiety levels. The purpose of this study was to determine the relationship of anxiety factors with anxiety levels. This research uses analytic research design with cross sectional approach. Sampling using accidental sampling. This research was conducted at Polindes Gerung Utara. Data analysis used chi square test. The results of the majority of respondents aged 31-35 years as many as 25 people (48.1%), the majority of high school education 32 people (61.5%), the majority of respondents earn Rp. 1000,000.00-Rp. 2000,000.00 as many as 29 people (55.8%). the majority of wife and fetal safety factors influence 40 people (76.1%), the majority sex expectation influences 27 people (51.9%), the financial responsibility factor has no influence of 28 people (53.8%) and on the factor of child birth defects there is the influence of 31 people (59.6%). Conclusion there is a relationship between the safety factor of the wife and the fetus with the level of anxiety (p = 0.04), there is a relationship between the sex expectation factor and the level of anxiety (p = 0.025), there is no relationship between the financial responsibility factor and the level of anxiety (p = 0.254), there is a relationship between birth defects and anxiety levels (p = 0.004). The results there are 3 factors that are associated with the level of anxiety of the husband.